Pengontrolan Robot Bulu Tangkis menggunakan Mikrokontroller ATmega128 berbasis Android Mobile - Yusuf Sofyan; Muhammad Ihsan; Sofy Fitriani (Journal of Computer System and Informatics (JoSYC), 2023)
In Indonesia, badminton was one of the most popular sport in various circles. Along with the times, robots can be designed as a device that can be used to play badminton. Robominton was badminton robot which is operated manually by human using a remote control or fully automatic. For a robot that controlled by manual-based, bluetooth or cable connection using joystick was used. This refers to the rules that have been set by DIKTI in “Robot Abu Indonesia (KRAI) 2015” Contest. As for the robot control system that we develop, are robotic system with manual control using android as a transmitter and bluetooth module HC-05 as a receiver. There is a robotic navigation control systems, transmission control systems shuttlecock, shuttlecock and servicing of control systems. ATmega 128 processor, four DC motors, with the EMS driver 30A H-Bridges was used as a hardware on shuttlecock transmission syste,. For shuttlecock services, self-designed pneumatic driver with solenoid valve was used. From the test results, the robot was able to navigate premises 11 formation movement, five pieces of shuttlecock transmission, and can serve up and down with a pneumatic